FRI0589 The Impact of Gout Flares on Patient-Reported Assessments of Pain and Disability. (15th July 2016) - Khanna, P.; Baumgartner, S.; Robinson, J.; Tafesse, E.; Morlock, R.
Abstract : Background: Lesinurad (RDEA594) is a selective uric acid reabsorption inhibitor (SURI) investigated for the treatment of gout in combination with xanthine oxidase inhibitors. In two Phase 3 clinical trials examining lesinurad in combination with allopurinol, patients with non-tophaceous gout demonstrated a reduction in gout flares over the 12-month study periods. Objectives: Investigate the relationship between gout flares and patient-reported assessments of pain and disability during the first 3 and last 3 months of two 1-year clinical trials assessing lesinurad in non-tophaceous gout patients with inadequate response to standard of care (NCT01510158 and NCT01493531 ). Methods: CLEAR 1 and CLEAR 2 were 12-month, randomized, double-blind, phase III trials to evaluate lesinurad (200 mg or 400 mg oral, daily) in combination with allopurinol (ALLO) vs ALLO + placebo. Gout flares were collected using an electronic patient diary and all flares reported in the diary were assessed. Patient-reported assessments of pain and disability included a Global Pain Scale and the HAQ-DI. A global measure of health utilty, the SF-6D, was derived from the SF-36v2. A pooled analysis of non-tophaceous patients in CLEAR 1 and CLEAR 2 assessed patient-reported measures for those with 0 flares, 1 flare, 2 flares and 3 or more flares, across treatment arms, during the first 3 months of the study (months 1 to 3) and during the final 3 months of the study (months 10 to 12), irrespective of treatment. Results: Patients in the CLEAR 1 and CLEAR 2 clinical trials (N=1062) were primarily male (94.8%), mean±SD age was 51.5±11.1 years and duration since gout diagnosis was 11.1±9.1 years. Most patients (87.8%) received ALLO 300 mg (range: 200–900 mg) daily. Irrespective of treatment, during the first 3 months of the study 41%, 22%, 15% and 22% patients reported 0, 1, 2 and 3 or more flares, respectively. During the final 3 months of the study 61%, 19%, 9% and 11% patients reported 0, 1, 2 and 3 or more flares, respectively. For both the HAQ-DI and Pain VAS, during the first 3 months and last 3 months of the study, the best (lowest) HAQ-DI and Pain VAS scores were reported in patients with 0 flares and the worst (highest) scores were reported in patients with 3 or more flares. The best (highest) SF-6D health utility scores, during the first 3 months and last 3 months of the study, were found in patients with no flares and the worst (lowest) scores were found in those with 3 or more flares. Conclusions: Non-tophaceous patients with the lowest number of flares, during the first and last 3 months of treatment, reported the most favorable HAQ-DI, pain and health utility measures. A majority of patients experiences zero flares during the final 3 months of the study period. Acknowledgement: Research sponsored by Ardea Biosciences/AstraZeneca. Editorial support was provided by PAREXEL and funded by AstraZeneca. Disclosure of Interest: P. Khanna Grant/research support from: AstraZeneca, S. Baumgartner Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group, J. Robinson Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group, E. Tafesse Employee of: AstraZeneca, R. Morlock Employee of: AstraZeneca